Effects of elevated CO2 concentrations and fly ash amended soils on trace element accumulation and translocation among roots, stems and seeds of Glycine max (L.) Merr. - Rodriguez, Judith Hebelen (2011)
The carbon dioxide (CO2) levels of the global atmosphere and the emissions of heavy metals have risen in recent decades, and these increases are expected to produce an impact on crops and thereby affect yield and food safety. In this study, the effects of elevated CO2 and fly ash amended soils on trace element accumulation and translocation in the root, stem and seed compartments in soybean [Glycine max (L.) Merr.] were evaluated. Soybean plants grown in fly ash (FA) amended soil (0, 1, 10, 15, and 25% FA) at two CO2 regimes (400 and 600 ppm) in controlled environmental chambers were analyzed at the maturity stage for their trace element contents. The concentrations of Br, Co, Cu, Fe, Mn, Ni, Pb and Zn in roots, stems and seeds in soybeans were investigated and their potential risk to the health of consumers was estimated. The results showed that high levels of CO2 and lower concentrations of FA in soils were associated with an increase in biomass. For all the elements analyzed except Pb, their accumulation in soybean plants was higher at elevated CO2 than at ambient concentrations. In most treatments, the highest concentrations of Br, Co, Cu, Fe, Mn, and Pb were found in the roots, with a strong combined effect of elevated CO2 and 1% of FA amended soils on Pb accumulation (above maximum permitted levels) and translocation to seeds being observed. In relation to non-carcinogenic risks, target hazard quotients (TQHs) were significant in a Chinese individual for Mn, Fe and Pb. Also, the increased health risk due to the added effects of the trace elements studied was significant for Chinese consumers. According to these results, soybean plants grown for human consumption under future conditions of elevated CO2 and FA amended soils may represent a toxicological hazard. Therefore, more research should be carried out with respect to food consumption (plants and animals) under these conditions and their consequences for human health.